Application of an adapted single-/half- effect NH3/H2O absorption chiller in tri-generation and solar cooling systems. (October 2018) - Neyer, Daniel; Ostheimer, Manuel; Hauer, Norbert; Halmdienst, Christian; Pink, Werner
Highlights: A single/half effect ammonia/water absorption chiller was developed. This concept allows heat rejection up to 45 °C and enables the application of dry coolers. Steady state and dynamic behaviour was evaluated with Hardware-in-the-Loop tests. Results are promising and show stable operation over a wide range of conditions. The half effect concept provides benefits for CHP and solar driven cooling applications. Abstract: Nowadays cooling loads make a considerable contribution of total energy consumption. Therefore, the focus has to be on the development of efficient sustainable cooling systems. This paper analyses the influence of different heat rejection units to a solar- or CHP-driven single-/half- effect ammonia/water absorption chiller. A functional model of the chiller based on flat plate heat exchangers which is switchable between single- and half effect is built and measured. Chiller performance is evaluated in Hardware-in-the-Loop tests in terms of steady state and dynamic tests. Advanced component models based on lookup tables with dynamic behaviour are derived and used for annual simulations. TRNSYS simulation studies are used to analyse the annual impact on technical and economic performance of the new single-/half- effect concept in various configurations and boundary conditions. The single/half effect chiller shows a good and stable performance over a wide range of operating conditions. It offers an operation up to 45 °C heat rejection temperature and enables the usage of a dry cooler in hot and arid climates. The application for solar- and CHP driven systems are reaching non-renewable primary energy savings of 30–70% at almost equal costs compared to conventional systems.